Poster making workshop using Canva as a science teaching media integrated with characters in elementary school - Lutfauziah, Asmaul; Fitriyah, Fifi Khoirul; Saputri, Tiyas; Wahyudi, Agus; Muharromah, Lailatul (UKInstitute, 2025)
The workshop was initiated in response to challenges faced by elementary school teachers in remote and underdeveloped regions, who often struggle with selecting appropriate teaching media. Additionally, elementary students in these areas tend to spend excessive time on gadgets without using them for learning purposes. This study aims to educate teachers on creating science posters using Canva, thus fostering character development and promoting the wise use of technology for learning. The project-based workshop included several stages: a Forum Group Discussion (FGD) to align the teachers' understanding, project-based learning planning, poster creation using Canva, and ongoing monitoring and evaluation. The program successfully enhanced the digital literacy and design skills of teachers to create poster integrated with character. The Canva design workshop was held virtually via Zoom, focusing on open media, learning posters, module covers, and learning videos. This activity was attended by teachers from various regions. The program lasted for two sessions (theory and practice of making products). The program has succeeded in helping teachers improve their creative design skills amidst limited access to technology in remote and outermost areas. The teachers managed to operate Canva well, showing high enthusiasm in improving their design skills. The evaluation showed high participant satisfaction, with 57% satisfied and 43% very satisfied. This workshop has succeeded in encouraging teachers to be more creative and innovative in the technology-based learning process.Abstrak. Lokakarya ini digagas sebagai respons terhadap tantangan yang dihadapi oleh guru-guru SD di daerah terpencil dan terbelakang, yang sering kali kesulitan dalam memilih media pembelajaran yang tepat. Selain itu, siswa SD di daerah tersebut cenderung menghabiskan waktu yang berlebihan pada gadget tanpa menggunakannya untuk tujuan pembelajaran. Penelitian ini bertujuan untuk mendidik guru-guru dalam membuat poster sains menggunakan Canva, sehingga menumbuhkan karakter dan mempromosikan penggunaan teknologi yang bijaksana untuk pembelajaran. Lokakarya berbasis proyek ini mencakup beberapa tahap: Diskusi Kelompok Forum (FGD) untuk menyelaraskan pemahaman guru, perencanaan pembelajaran berbasis proyek, pembuatan poster menggunakan Canva, dan pemantauan dan evaluasi berkelanjutan. Program ini berhasil meningkatkan literasi digital dan keterampilan desain guru untuk membuat poster yang terintegrasi dengan karakter. Lokakarya desain Canva diadakan secara virtual melalui Zoom, dengan fokus pada media terbuka, poster pembelajaran, sampul modul, dan video pembelajaran. Kegiatan ini diikuti oleh guru-guru dari berbagai daerah. Program berlangsung selama dua sesi (teori dan praktik membuat produk). Program ini telah berhasil membantu guru meningkatkan keterampilan desain kreatif mereka di tengah keterbatasan akses teknologi di daerah terpencil dan terluar. Para guru berhasil mengoperasikan Canva dengan baik, menunjukkan antusiasme yang tinggi dalam meningkatkan keterampilan desain mereka. Hasil evaluasi menunjukkan kepuasan peserta yang tinggi, dengan persentase 57% puas dan 43% sangat puas. Workshop ini berhasil mendorong guru untuk lebih kreatif dan inovatif dalam proses pembelajaran berbasis teknologi.